Edukasi Penggunaan Obat dan Herbal Tradisional yang Aman pada Diabetes Mellitus bagi Siswa SMK Muhammadiyah 3 Terpadu Pekanbaru - Restu Anisa Putri; Ayu Rahmawati; Nursyafni Lubis; Novtafia Endri (Universitas Mataram, 2026)
Diabetes mellitus is a chronic disease that requires proper management, including correct medication use. Early education for vocational high school students is important to build awareness about safe medication use. The purpose of this community service activity was to increase students' knowledge about the safe use of diabetes mellitus medications, including Beyond Use Date (BUD), insulin storage, and traditional herbal medicines. The method used was lectures and discussions with a pre-post test design. Respondents were 32 grade X students from SMK Muhammadiyah 3 Terpadu Pekanbaru. Data were analyzed using paired t-test. Results showed a significant increase in knowledge scores from 73.98±3.13 to 87.04±7.47 (p<0.001) with Cohen's d=1.76. The proportion of students with good knowledge category increased from 3.1% to 81.2%. This education program was highly effective in increasing students' knowledge about the safe use of diabetes mellitus medications.